Optimalisasi Penjernihan Air PDAM Tirta Meulaboh Menggunakan Aluminium Sulfat (Tawas) dan Poly Aluminium Chloride (PAC) - Marlinda Marlinda; Rita Hartati; Yusi Hidjrawan; Kasmawati Kasmawati (Jurnal Optimalisasi, 2023)
This research aimed to determine the optimum coagulant that can be used to purify PDAM Tirta Meulaboh water which often has a cloudy color during the rainy season. The coagulants used are PAC and Tawas with the chemical formula Al2(SO4)3 and Poly Aluminum Chloride is known as PAC with the chemical formula Aln(OH)mCl(3n-m). The test was carried out by mixing 10 grams of alum and PAC which were dissolved in 1000 mL of water/aquades each. The treatment was carried out by dissolving each 1 mL in 1000 mL of PDAM water sample equal to 10 ppm. Variations in the addition of PAC/alum to each container were 10, 20, 30, 40, 50 and 60 ppm. Furthermore, rapid mixing was carried out at a speed of 100-150 rpm and slow at 20 rpm. The results showed that 10 ppm of PAC added to the sample produced turbidity of 5.2 NTU and pH 7.8, 20 ppm: 4.1 NTU and pH 7.5, 30 ppm: 3.8 NTU pH 7.3, 40 ppm : 2.3 NTU pH 7.2, 50 ppm: 1.5 NTU pH 7.1, 60 ppm: 0.8 NTU and pH 7.0. Samples added with 10 ppm of alum produced turbidity of 5.5 and pH 6.8, 20 ppm: 5.1 pH 6.7, 30 ppm: 4.5 pH 6.6, 40 ppm: 3.2 pH 6.6 , 50 ppm: 4.3 pH 6.4 and 60 ppm: 5.0 pH 6.3. The conclusions from this study indicate that PAC and alum coagulants can affect turbidity and pH levels of water, the optimal addition of PAC coagulant to purify water is 20 ppm, while the optimal addition of alum coagulant to purify water is 30 ppm.